Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Menulis Teks Ulasan Pada Siswa Kelas XII SMA Negeri 1 Pekanbaru Tahun Pembelajaran 2023/2024 - Anfilla Tahany; Finanta Okmayura; Khairunnisah Khairunnisah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the effect of the Problem Based Learning learning model on review text writing skills in class XII students at SMA Negeri 1 Pekanbaru and to find out how the Problem Based Learning learning model is applied to review text writing skills in class the type of research carried out in this research is a Quantitative Approach. The population in this study was all students in class. The data collection technique used in this research is the test and observation method. Data Analysis Techniques In this research the author uses quantitative descriptive. The research results in this study are the value of review text writing skills studied using the Problem Based Learning method, meaning that the average percentage of student scores is 85.00 ≥ 100% of the specified KKM, so it can be concluded that H1 is accepted and H0 is rejected and there is an influence on Value of review text writing skills for class XII students at SMA Negeri 1 Pekanbaru. The results of hypothesis testing use the t test, namely the Independent Sample T-Test via the SPSS program. shows that t count ≥ table, namely 128.567 > 2.036 with df = 32 at the 5% significance level is 2.036 so that H1 is accepted and Ho is rejected.